The politics of judicial review in inter-war Europe - Bubenheimer, F (2021)
Why do some politicians choose to tie their own hands by empowering courts to review the constitutionality of legislation? This is a persistent question in judicial politics. According to a popular rational choice theory, politicians accept judicial constraints on their power because they seek “insurance” against costs they might incur during future periods in opposition. Hence, the key variable favouring support for judicial review is electoral alternation.